Taṭwīr Muḥtawā Ta‘līm Al-Lughah Al-‘Arabiyyah Lil-Marḥalah Al-Thānawiyyah Bi-Indūnīsiyā Fī Ḍaw’ Al-Manhaj Al-Qā’im ‘Alā Al-Ḥubb Al-Ṣādir ‘An Wizārat Al-Shu’ūn Al-Dīniyyah Al-Indūnīsiyyah - Burhan Yusuf Habibi; Sayed Mostafa Ebead (UIN ANTASARI, 2026)
This study aims to propose a framework for developing Arabic language teaching content for the secondary level in Indonesia in light of the love-based curriculum issued by the Indonesian Ministry of Religious Affairs. The study addresses the dominance of formal linguistic aspects in Arabic textbooks and the limited integration of affective values, despite the important role of Arabic in religious educational institutions. The research employed the descriptive-analytical method using content analysis to examine a secondary-level Arabic textbook based on indicators of love-based values: love of God and His Messenger (peace be upon him), love of knowledge, self-love, love of others, love of the world/environment, and love of the homeland. The findings reveal that these values appear at varying levels within the content; some are presented partially and without systematic planning, while others remain weak or absent, particularly the values of love of knowledge, self-love, and love of the world/environment. The study proposes a framework integrating linguistic and value-based objectives and reconstructing texts, activities, and assessment methods to support balanced learner development.